KECEMASAN DALAM PROSES BELAJAR - Mukholil Mukholil (Universitas Muhammadiyah Kotabumi, 2018)
Anxiety is the manifestation of mixed emotion which is expeienced by someone as a reaction toward threat, pressure, and worry which affect both physical and psychological. There are various kinds of anxiety, such as the anxiety of having done mistakes or sins; anxiety of having seen and felt danger and the anxiety in the unclear form. The symptoms of anxiety can be in the physical or psychological form. Anxiety can disturb students’ learning process. However, low level anxiety can motivate students to get better achievement.